Correlation of sleep quality with anthropometric parameters in young healthy individuals - Babu, Rose; Bahuleyan, Biju (International Journal of Research in Medical Sciences, 2018)
Background: Obesity, which is the harbinger of various diseases, is considered as the epidemic of this era. Various lifestyle changes have resulted in a younger generation being prone to obesity. On investigating the etiology of obesity in young individuals, besides the change in food habits, sleep has also found a place. Various investigators have come up with conflicting results regarding the correlation between sleep and anthropometric parameters. In this backdrop, the present study was planned to analyze the correlation of sleep quality with anthropometric parameters. Methods: 100 first year MBBS students were given the Pittsburgh sleep questionnaire which gives a self-reported assessment of their sleep quality. Anthropometric parameters of the students were recorded along with body fat analysis using Omron body fat analyzer. The results obtained were tabulated and analyzed. Results: Out of the 100 students 45 were found to be poor sleepers. On analyzing the anthropometric parameters, no significant difference was noted between good sleepers and poor sleepers. The body fat content also did not show any significant difference between the two groups. Conclusions: The findings of the present study show a nonmonotonic relationship between sleep quality and anthropometric parameters. This shows that the response of the adolescent population may differ in comparison with other groups. Hence it is recommended that the poor sleepers in the adolescent group need to be followed up in future.